Culturally Responsive Teaching Instrument Development to Increase CultureInvolvement in Teaching - Irdiyansyah, Iyan; Rosdiana, Rina; Chodijah, Siti; Mardiani, Dini; Rahmadani, Eneng Syifa (Universitas Islam Negeri Raden Fatah Palembang, South Sumatra, Indonesia, 2025)
Culturally Responsive Teaching (CRT) is a pedagogical approach that emphasizes the importanceof considering students' cultural backgrounds in the learning process in order to create an inclusive,equitable and effective learning environment. This study aims to develop a valid and reliable CRTpractice measurement instrument in accordance with the Indonesian educational context. Theresearch method used was Research and Development (R&D) with the Four-D model (Define,Design, Develop, Disseminate). The instrument was developed based on literature review andexpert validation, then tested on Teacher Professional Education Program (PPG) students throughvalidity and reliability analysis. The validity test results using Aiken's V showed that 20 out of 24statement items were declared valid, while the reliability test resulted in a Cronbach's Alpha valueof 0.984 which showed a very high level of internal consistency. The resulting CRT instrumentincludes five main dimensions, namely Validating, Multidimensional, Empowering,Transformative, and Emancipatory. This instrument can be used by teachers, researchers andpolicy makers to assess and improve the implementation of culturally responsive learning, as wellas a basis for the development of more inclusive and contextualized education policies inIndonesia.